Impact of “noncaloric” activity-related factors on the predisposition to obesity in children - Angelo Tremblay; Émilie Pérusse-Lachance; Patrice Brassard (Risk Management and Healthcare Policy, 2010)
Angelo Tremblay, Émilie Pérusse-Lachance, Patrice BrassardDivision de Kinésiologie, PEPS, Université Laval and Centre de Recherche de l’Institut Universitaire en Cardiologie et Pneumologie de Québec, Québec, CanadaAbstract: The research related to childhood obesity generally emphasizes the impact of unhealthy eating and sedentary behavior as the main determinants of the predisposition to the positive energy balance that underlies excess body fat accumulation. Recent investigations have, however, demonstrated that “noncaloric” activity-related factors can induce a significant imbalance between spontaneous energy intake and energy expenditure. This is the case for short sleep duration that favors hormonal changes that increase hunger and energy intake. This agrees with our research experience demonstrating that short sleeping predicts the risk of obesity in children to a greater extent than sedentary behavior. Recent research by our team has also showed that demanding mental work promotes a substantial increase in energy intake without altering energy expenditure. In addition, our preliminary data suggest that the regular practice of school-related cognitive efforts is predictive of an increase in abdominal fat accumulation. As discussed in this paper, individual variations in brain oxygenation and its related cerebral aerobic fitness might play a role in the relationship between mental work, energy intake, and the risk of excess body weight.Keywords: sleep duration, mental work, brain oxygenation, energy intake, energy expenditure